AN ERRORS ANALYSIS IN FORMING PLURAL OF NOUNS AT SMPS PELITA NUSANTARA TANJUNGPINANG - Joko Iswanto; Eka Mayasari; Rika Febria (Universitas Negeri Islam Sumatera Utara, 2022)
This research aims to analyse the learners’ errors in their process of second language learning. The problem of this research was the students did not understand and could not apply the right rules for changing the plural form from its singular. The Purpose of this research was to see the errors made by the seventh-grade students of SMPS Pelita Nusantara which consists of 16 students in forming the plural of nouns and to find the causing factors of errors made by them. The method of this research was descriptive qualitative research. The technique to collect the data, the researcher distributed essay tests and open-ended questions. The technique to analyze this research were collecting the data from students’ work, identifying the students’ error by underlining the error items, classifying the students’ errors based on surface strategy taxonomy, explaining the students’ errors, calculating the percentage of each error. The result of the tests was most of the students made errors on the type of irregular forms because the rules of irregular were more complicated. The factors of students’ errors in regular plural because they did not understand and forgot the rules and made them confused to change the word from singular into plural forms. Keywords: Error Analysis; Plural form; Nouns.